NIKOTIN DAN EKSPRESI PROTEIN 2 UCP2 PENGARUH TERHADAP ISKEMIKSTROKE - Anwar Wardy W* (Neurona Majalah Kedokteran Neuro Sains, 2009)
NICOTINE INDUCING WILL BE INCREASING THE EXPRESSION OF UCP2 IN WHITE ADIPOSE TISSUE AND MUSCLE CEREBRAL ARTERY CELL IT WAS SHOWN TO BE NEUROPROTECTIVE BOTH IN VITRO USING UCP2 TRANSECTED CELLS IN AN OXYGENGLUCOSE DEPRIVATION AND IN VIVO IN A TRANSGENIC MOUSE MIDDLE CEREBRAL ARTERY OCCLUSION